The Problem of the Criterion of Truth in the Pragmatism of William James - Patkauskaitė, Jūratė (Problemos, 1984)
In the article it is demonstrated how the pragmatic maxim of Ch. S. Peirce altered the significance in the psychological attitude of William James. W. James changed the classical conception of truth as the agreement of thoughts with reality by the concept of the stream of “pure experience” and proposed new synonyms for “agree”, namely, those of “working” of idea and “successful leading”. Thus he introduced a new pragmatic criterion of truth – satisfaction to the subject. The article traces the sources of the development of W. James’s idea in the context of pragmatism.